(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
This independent work analyzesthe concept of a scientific hypothesis, its role in the development of science and its importance in the scientific research process. A scientific hypothesis is a tentative solution put forward to solve a specific scientific problem, which is tested on an experimental or theoretical basis. The work covers the stages of the formation of a hypothesis, the requirements for it, and methods for proving and refuting a hypothesis. It also discusses the creation of new knowledge based on scientific hypotheses and its role in scientific methodology